The Study of Poetic Terms in Abid Shah Abid’s Urdu Poetry - khattak, Dr. Khalid Mahmood; Saddozai, Ms. Humera (Hanken, 2013)
Abid Shah Abid Balochistani was the poet of Barhvi, Persian and Urdu Languages. We can find the vast range of poetic expressions in his Urdu Poetry and its usage made his poetry more able and artistic beside it has made this poetic tradition strong in Balochistan and left foot steps for coming generations as well and on its base coming poets paid regard to Urdu poetry. Poetic Expression con is seen with uniqueness. In this respect, Tashbihat, Istearat, Qafia, Radif, Matla, Maqta, Takhalus, Taraqeeb, Sana-e-lafzi and Masnavi are most important.